FROM ENHANCEMENT TO CONTINUITY: TRANSHUMANISM, POSTHUMANISM, AND THE EMERGENCE OF METAZŌIC ONTOLOGY IN THE AGE OF PLANETARY AND TECHNOLOGICAL BECOMING. (Journal of Teleological Science, 2026)
The current philosophical discussion on the future of humanity is mainly organized around two main paradigms: transhumanism and posthumanism. The former promotes the idea of human enhancement and transcendence over biological limitations, while the latter challenges anthropocentrism and seeks to redefine the human in terms of its embedded relation in ecological and technological networks. This article seeks to introduce the concept of Metazoic ontology, which differs from the above two paradigms in its emphasis on continuity rather than transcendence or decentering. The article will also introduce an epistemology of relation and care, a model of Metazoë as a multi-dimensional transcription, and a phenomenological-poetic approach, contextualizing these within the Tofflerian concept of acceleration, arguing that the current “future shock” is an epistemological crisis, especially in relation to the role of generative AI, platform memory, and planetary instability. The article will also argue that, in addition to the critique of anthropocentrism or the dream of human enhancement, there is an urgent need for an ontology of continuity that is capable of addressing issues related to digital persistence, ecological duration, and cultural hyper-memory, without falling into either techno-utopianism or dissolution. The concept of Metazoic ontology is an attempt in this direction, an ethics of continuity stewardship in terms of responsibility for the traces we leave behind.
Keywords: Transhumanism; Posthumanism; Metazoic Ontology; Cultural Memory; Metazoë; Ecological Duration; Artificial Intelligence; Digital Traces; Polytentacular Thinking